Pre-operative Considerations in Adult Mucopolysaccharidosis Patients Planned for Cardiac Intervention - Cross, Benjamin; Stepien, Karolina M.; Gadepalli, Chaitanya; Kharabish, Ahmed; Woolfson, Peter; Tol, Govind; Jenkins, Petra (Frontiers in Cardiovascular Medicine, 2022)
Mucopolysaccharidoses (MPS) are rare lysosomal storage diseases characterised by multiorgan involvement and shortened longevity. Due to advances in therapies such as enzyme replacement therapy and haematopoietic stem cell therapy, life expectancy has increased posing newer challenges to patients and health professionals. One such challenge is cardiovascular manifestations of MPS, which can be life limiting and cause reduction in quality of life. Any cardiovascular intervention mandates comprehensive, multi-systemic work-up by specialist teams to optimise outcome. We highlight the importance of multidisciplinary evaluation of adult MPS patients requiring cardiovascular intervention. Clinical assessments and investigations are discussed, with a focus on the cardiac, anaesthetic, airway, respiratory, radiological and psychosocial factors.